2021
DOI: 10.15407/ujpe66.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Functional Analysis of Electronic Properties of Transition-Metal Phthalocyanines

Abstract: This work presents the ab initio study of transition-metal phthalocyanines within a PBE0 hybrid functional. The list of metal impurities includes manganese, iron, cobalt, nickel, copper, and zinc. All calculations of isolated molecules have been performed with the use of the projector augment-wave method. For iron phthalocyanine, we have performed four calculations with different values of the mixing parameter a (the value of the exact exchange) – 0, 1/4, 1/3, and 1/2. For all other molecules, the calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…CoPc presents a greater possibility of interaction between CuPc and NoPc, for the three proteins considered in this study. This result may be related to the significant differences in the hybridization of the 3d states of Co and Cu transition elements with the states in the valence and conduction bands, as observed in the study of KLYSKO and SYROTYUK (2021) 140 . To assess docking results, it is conventional to use the lowest docking score which can create a better binding between the ligand and the protein.…”
Section: Resultsmentioning
confidence: 93%
“…CoPc presents a greater possibility of interaction between CuPc and NoPc, for the three proteins considered in this study. This result may be related to the significant differences in the hybridization of the 3d states of Co and Cu transition elements with the states in the valence and conduction bands, as observed in the study of KLYSKO and SYROTYUK (2021) 140 . To assess docking results, it is conventional to use the lowest docking score which can create a better binding between the ligand and the protein.…”
Section: Resultsmentioning
confidence: 93%
“…It was found that realistic band gaps, wave functions, and crystal potentials obtained with PBE0 hybrid functional [4] for the exchange-correlation energy al-lowed to obtain an electronic structure in nanostructures [5,6] that shows good comparison with the experiment. The use of the PBE0 hybrid functional made it possible to compare well the parameters of the electronic energy spectrum in a solid solution of CdMnTe [7] with the measured values [8].…”
Section: Introductionmentioning
confidence: 95%
“…The recommended value of the mixing factor  is equal to 0.25. In formula (5), the exchange energy, in which the SIE of 3d electrons is the largest, is partially subtracted. In fact, these electrons move in narrow energy bands with a high density of states (DOS).…”
Section: Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“… is important for describing materials containing d (f) electrons. In particular, it has been successfully used to study nanostructures containing transition 3d elements [13,14]. Energy band structure peculiarities and luminescent parameters of CeX 3 (X = Cl, Br, I) crystals were revealed and shown good comparison with experiment [15].…”
mentioning
confidence: 99%